2017
DOI: 10.5812/aapm.45297
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Efficacy of Oral Memantine and Placebo for Acute Postoperative Pain in Patients Undergoing Dacryocystorhinostomy (DCR)

Abstract: BackgroundMemantine is an N-methyl-D-Aspartate (NMDA) antagonist. By transferring acute postoperative pain, the NMDA channels may lead to active excess and neuropathic pain. Objectives: This study attempted to investigate the effect of preoperative use of single oral dose of memantine in controlling Dacryocystorhinostomy (DCR) postoperative pain.MethodsA double-blind clinical trial was conducted on 60 patients undergoing DCR. On arrival at the operating room, the memantine group received 20 mg of oral memantin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Memantine can be used in doses starting from 5 mg to 30 mg with a gradual increase over a week, and we used 20 mg for this study as per a previous study. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Memantine can be used in doses starting from 5 mg to 30 mg with a gradual increase over a week, and we used 20 mg for this study as per a previous study. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Rahimzadeh et al . [ 6 ] found that when memantine was administered just before induction, visual analogue scores were less at 1 h, 2 h and 6 h postoperatively in dacrocystorhinostomy, and this might have been because of the shorter duration of the procedure. In a study by Taheri et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have reported the effect of postoperative administration of non-opioid medications ( 22 - 25 ), including acetaminophen ( 26 - 30 ), on the postoperative pain, and opioid sparing. However, the efficacy of preoperative administration of acetaminophen on pain after surgery was reported only by limited studies ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when utilized as an adjuvant with opioids, ketamine can improve postoperative analgesia and reduce total morphine consumption in patients undergoing thoracic and abdominal surgeries (13,14). Memantine, amantadine, and dextromethorphan do not have the same extensive list of adverse side effects compared to ketamine and methadone, but they also do not show linear longterm reduction of pain (15)(16)(17).…”
Section: Nmda Antagonistsmentioning
confidence: 99%